Fósforos ante la pantalla (secuencias paralelas) - Perea, Héctor (Anales de Literatura Hispanoamericana, 2003)
This essay is about Alfonso Reyes, Martín Luis Guzmán and Carlos Fuentes as motion picture critics, adapted authors and cinema writers. All of them shared the same pseudoymous: Fósforo. Although Fuentes signed his articles on behalf Reyes as Fósforo II. Their contributions were very important not only for the cinema criticism growth in Spanish, but also for the mexican cinema modernization.